O Papel do diálogo colaborativo no aperfeiçoamento da interlíngua de alunos brasileiros (nível básico de inglês como língua estrangeira) - Diniz, Sébora Seny Sarmento Fernandes (2010)
This research addresses the importance of negotiation of form in communicative classes of English as a foreign language. Based on the concept of focus on form and on the output hypothesis from the perspective of sociocultural theory, I examine the collaborative dialogue of basic-level students from a conversation course in English as a foreign language. The language-related episodes identified in the collaborative dialogue and the written production of the students made before and after the collaborative dialogue are qualitatively analyzed in two ways: first, by observing how students deal with their language problems, I seek evidence of the use of collaborative dialogue as a cognitive tool; and then, by observing the use of communication strategies, I investigate the collaborative dialogue as a communicative tool. The data were collected in three steps: (a) production of written task 1 (b) collaborative dialogue (recorded and transcribed for analysis), and (c) production of written task 2 (reformulation of the written task 1). Besides the possibility of registering the collaborative dialogue among students from basic-level English in the target language to serve as communicative practice, the results point to the effectiveness of using this procedure in improving the interlanguage of these learners and suggest the benefit of the inclusion of tasks focusing on form involving negotiation via collaborative dialogue in communicative classes of English as a foreign language.